Laporan Keuangan UMKM Berdasarkan SAK EMKM di Desa Klambir Lima Kebun Kecamatan Hamparan Perak - Teuku Radhifan Syauqi; Destari Damanik; Hanif Ramadhan (JURNAL AKUNTANSI AUDIT DAN PERPAJAKAN INDONESIA (JAAPI), 2024)
This study aims to analyze the process of preparing financial statements in Micro, Small and Medium Enterprises (MSMEs) based on the Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM). SAK EMKM is designed to make it easier for MSMEs to prepare financial reports in accordance with applicable accounting standards, so as to increase transparency, accessibility to financing, and better decision making. The research method used a qualitative-descriptive approach with data collection through interviews, observations, and document studies. The research subjects involved MSME actors from various business sectors located in the research area. The main focus is on business actors' understanding of SAK EMKM, challenges in its implementation, and perceived benefits.